Classic biphasic pulmonary blastoma: A case report and review of the literature. (May 2018) - Le Caer, H.; Teissier, E.; Barriere, J.R.; Venissac, N.
Abstract: Pulmonary blastomas represent about 0.5% of primary pulmonary malignancies. The prognosis is poor. Standard treatment consists of surgical excision. There are no published series on which to judge the efficacy of chemotherapy or radiation therapy. We describe an unusual case of classic biphasic pulmonary blastoma (CBPC), with long-term survival despite numerous and varied cancer-related events and review the literature. Our 71-year-old Caucasian woman presented with history of blood in sputum in 2009. Right lower lobectomy yielded a diagnosis of sarcomatoid carcinoma (pneumoblastoma). Unusually, our patient is still alive 7 years after initial surgery, despite metastatic first relapse after 2 years. Metastatic progression was confirmed histologically on three separate occasions during the disease course. The patient received a combination of cisplatin (or carboplatin) and etoposide on three separate occasions. Molecular biology studies of CBPC are needed to identify effective treatments, and a patient registry should be created.